Will China build tomorrow's Britain? Examining the impacts of Brexit and the skills crisis. Issue 1 (2nd January 2017) - Sweet, Rod; Smith, David
Abstract : At a time when the UK construction workforce should be expanding and up-skilling to meet new demand for homes and critical infrastructure, underlying demographic trends are causing it to shrink. Oft-repeated warnings about skills shortages are now joined by fears over the impact of Brexit, which could restrict even further the UK's access to skills. Examining the rising demand for construction services against the industry's chronic structural weaknesses, this essay asks whether British contractors are at risk of being sidelined by bigger and better capitalised foreign firms, particularly from China, who are able to deploy vast reserves of both technical expertise and labour.